Implementasi Media Fun Match Board dalam Pembelajaran IPS di Kelas 3 SDN Benua Anyar 10 - Fatimatuz Zhahra; Hutri Hidayah; Fatmah Rogayah; Aldy Ferdiyansyah (Journal of Character and ELementary Education, 2026)
Social Studies is an important subject in Elementary School that aims to shape students' understanding of social, cultural, economic, and civic life, but learning is still dominated by lecture methods without media so that students are less active and have difficulty understanding the material. This study aims to identify problems in IPS learning in grade 3 of SDN Benua Anyar 10 and implement the Fun Match Board media as an innovative solution. This study uses a descriptive qualitative approach with a case study method. Data collection techniques are carried out through observation, interviews, and documentation, and analyzed using triangulation. The results of the study show that after using the Fun Match Board, student learning motivation, learning outcomes, and activeness increased. This media successfully created an interactive, fun, and contextual learning atmosphere. Fun Match Board is worthy of being used as an effective alternative learning media in supporting the quality of IPS learning in elementary schools.